Analisis Perhitungan Pajak Penghasilan Terutang Pt Stepa Wirausaha Adiguna Untuk Tahun 2017 - Karissa Oktavia, Purnamawati Helen Widjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research uses PT Stepa Wirausaha Adiguna located on the island of Belitung as the object of research. The purpose of this study is to determine the truth of the corporate income tax calculation carried out by the company, including fiscal correction and total fiscal profit / loss owned by the company. The research method used in this research is descriptive method, using primary data which is then processed through observation, interviews and documentation, then in the final stage an analysis is carried out on the data.The results of this research are that the company has calculated and made all fiscal and total corrections of fiscal profit / loss appropriately, however in the calculation of income tax there is a mistake. This is related to the calculation of this tax that is not rounded up on Taxable Income, which causes errors and the result of the Accrued Income Tax by the company is incorrect.